Status and impacts to sea turtles in Vietnam - Nguyen, Dang Ngai; Pham, Van Chien (Vietnam Journal of Marine Science and Technology, 2024)
Sea turtles face a great danger of extinction because of human impacts, and the number of turtle occurrence is decreasing. By interviewing fishermen, coastal residents and authorities combined with field surveys in some places where turtles regularly lay eggs, such as Con Dao and Ninh Thuan, the results show that 05 species of sea turtles were found in Vietnam: The Green (Chelonia mydas), Hawksbill (Eretmochelys imbricata), Olive Ridley (Lepidochelys olivacea), Loggerhead (Caretta caretta) and Leatherback (Dermochelys coriacea). Among them, Green turtles are the most abundant and distributed in all surveyed localities; Hawksbill and Olive Ridley were smaller in number; and Loggerhead and Leatherback were the two species with the least number. Only 03 species remaining to breed on the beaches: Green, Olive Ridley, and Leatherback. The Hawksbill turtles used to lay eggs in the past but have been no longer recorded. Con Dao is a home for the largest number of breeding Green turtles. The reasons for the decline of turtles in Vietnam were the collection of eggs and nesting turtles, fisheries bycatch, development of coastal infrastructure and waste pollution, habitat degradation, and illegal trade in sea turtle products.